Evaluación de la aplicación del módulo contable Sistema Integrado de Administración Financiera Sistema Presupuestario SIAF SP en la Universidad Nacional de San Martín, periodo 2013 - Capillo Ruiz, Anel Ingrid (2014)
The purpose of this research is on. "Evaluate the accounting that affect the application of module SIAF - SP at the National University of San Martín. Period 2013". This goal responds to the main problem in the sense of what these characteristics for which the following hypothesis has been raised. "Application of accounting module SIAF - SP favorably affects the results of the accounting of the operations of budgetary implementation of the Universidad Nacional de San Martín. Period 2013". The methodology used is based on the selection of a sample of intentional type or convenience constituted by the staff that works in the accounting unit in number of five (05) , linked to the progresses of this module. For this type of research is applied at the descriptive level and the design of it is non-Experimental type transactional Descriptive, than through the use of the analytical method - synthetic and descriptive methods and regulatory as well as of techniques and instruments of collection, processing and analysis of data, have allowed the verification of the hypothesis, i.e. through documentary analysis. The results of research through documentary analysis, shows that the application of the accounting module SIAF - SP has favorably impacted on administrative records of income and expenditure and its consolidation accounting for budgetary and financia! statements.